The Reduced Adaptability of H-Reflex Parameters to Postural Change With Deficiency of Foot Plantar Sensitivity - Sun, Mengzi; Lewis, Kelsey; Choi, Jung Hun; Zhang, Fangtong; Qu, Feng; Li, Li (Frontiers in Physiology, 2022)
Purpose: The project was to examine the influence of peripheral neuropathy (PN) severity on the relationship between Hoffmann-reflex (H-reflex) and postures. Methods: A total of 34 participants were recruited. H-reflex (H/M ratio and H-index) during prone, standing, and the heel-contact phase of walking was tested, along with foot sole sensitivity. Results: The participants were divided into three groups based on the severity of the foot sole sensitivity deficit: control, less (LA), and more (MA) affected with both feet 5.07 monofilament test scores ranging 10, 0–5, and 6–9, respectively. A significant group by the posture interaction was observed in the H/M ratio (F3.0, 41.9 = 2.904, p = 0.046, ηp2 = 0.172). In the control group, the H/M ratio of prone (22 ± 7%) was greater than that of the standing (13 ± 3%, p = 0.013) and heel-contact phase (10 ± 2%, p = 0.004). In the MA group, the H/M ratio of standing (13 ± 3%) was greater than that of the heel-contact phase (8 ± 2%, p = 0.011). The H-index was significantly different among groups (F2,28 = 5.711, p = 0.008, and ηp2= 0.290). Post hoc analysis showed that the H-index of the control group (80.6 ± 11.3) was greater than that of the LA (69.8 ± 12.1, p = 0.021) and MA groups (62.0 ± 10.6, p = 0.003). Conclusion: In a non-PN population, the plantar sensory input plays an important role in maintaining standing postural control, while as for the PN population with foot sole sensitivity deficiency, type Ⅰ afferent fibers reflex loop (H-reflex) contributes more to the standing postural control. The H-index parameter is an excellent method to recognize the people with and without PN but not to distinguish the severity of PN with impaired foot sole sensitivity.